2022
DOI: 10.3390/foods11244104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidative Modification by Peroxyl Radical on the Characterization and Identification of Oxidative Aggregates and In Vitro Digestion Products of Walnut (Juglans regia L.) Protein Isolates

Abstract: Walnut protein is a key plant protein resource due to its high nutritional value, but walnuts are prone to oxidation during storage and processing. This article explored the oxidative modification and digestion mechanism of walnut protein isolates by peroxyl radical and obtained new findings. SDS-PAGE and spectral analysis were used to identify structural changes in the protein after oxidative modification, and LC-MS/MS was used to identify the digestion products. The findings demonstrated that as the AAPH con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Cys can be oxidised to cystine (protein cross‐linking agent), sulphate acid, sulphite acid and sulphonic acid. It was found that the decay rate of amino acids in oxidised walnut protein from high to low was Cys, Met, Tyr, Lys, His, Val and Pro (Zhao et al ., 2022). Moreover, Cys‐S‐S linkage produced by the reaction of cysteine with free sulphydryl groups may cause soluble protein aggregation.…”
Section: Current Understanding Of Oxidative Of Plant Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Cys can be oxidised to cystine (protein cross‐linking agent), sulphate acid, sulphite acid and sulphonic acid. It was found that the decay rate of amino acids in oxidised walnut protein from high to low was Cys, Met, Tyr, Lys, His, Val and Pro (Zhao et al ., 2022). Moreover, Cys‐S‐S linkage produced by the reaction of cysteine with free sulphydryl groups may cause soluble protein aggregation.…”
Section: Current Understanding Of Oxidative Of Plant Proteinmentioning
confidence: 99%
“…Studies have shown that when the time of oxidation of soybean protein by 2,2′‐azobis (2‐amidinopropane) dihydrochloride (AAPH) increased from 0 to 4 h, more internal hydrophobic groups were exposed, but with the further strengthening of oxidation, the oxidative attack changed the interaction and cross‐linking reaction of soybean protein and promoted the conversion of free sulphydryl groups into disulphide bonds, which induced the formation of polymer flexible oxidised aggregates with larger particle size (Guo et al ., 2022). Similarly, the oxidation results of walnut protein showed that tryptophan and free sulphydryl group decreased with increasing concentrations of oxygens, producing a large number of soluble aggregates, which may be due to the Cys‐s‐s linkage formed by the reversible reaction of free sulphydryl groups with cysteine (Zhao et al ., 2022).…”
Section: Factors Affecting Plant Protein Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the walnut isolate protein were placed in the freeze dryer at 4 • C for freezing. The protein content was measured as 86.53% by Kjeldahl (SKD-3000, Xi'an Yupu Instrument Co., Xi'an, China) [21].…”
Section: Preparation Of Walnut Proteinmentioning
confidence: 99%